Humidity-responsive deforming dynamic covalent polymers and methods of making the same

CN117247498BActive Publication Date: 2026-10-27SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311358405.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2026-10-27
Estimated Expiration
2043-10-18

Smart Images

  • Figure HDA0004502532400000011
    Figure HDA0004502532400000011
  • Figure HDA0004502532400000021
    Figure HDA0004502532400000021
  • Figure HDA0004502532400000031
    Figure HDA0004502532400000031
Patent Text Reader

Abstract

The application discloses a humidity-responsive deforming dynamic covalent polymer and a preparation method thereof, and the method comprises the following steps: dissolving an N-vinyl amide polymer in an organic solvent to obtain a linear polymer solution; adding a double-bond-containing phenylboronic acid monomer, a hydrophilic crosslinking agent and an initiator in sequence, stirring to completely dissolve, performing a free radical polymerization reaction, pouring in a polytetrafluoroethylene mold, heating and evaporating the solvent, and thus obtaining the humidity-responsive deforming dynamic covalent polymer. The dynamic covalent polymer prepared by the application has excellent mechanical properties, self-repairing properties, recyclability, shape memory properties, humidity-induced solid-state plastic deformation and humidity-responsive deformation properties. The application solves the problems that the dynamic covalent polymer-based deforming material in the prior art is difficult to realize complex programmable and reversible deformation behavior and has poor durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of smart polymer preparation technology, specifically to a humidity-responsive deformation dynamic covalent polymer and its preparation method. Background Technology

[0002] Inspired by various deformation behaviors in nature, materials capable of deformation under external stimuli (such as humidity, temperature, magnetic fields, light, electric fields, and solvents) have been extensively studied and show potential applications in flexible electronics, soft robotics, and sensors. Among them, shape memory polymers (MMBs) have advantages such as large deformation, light weight, high recovery stress, and fast response speed, making them the most important research object in the field of deformable materials. Shape memory polymers can generally be divided into thermosetting shape memory polymers and thermoplastic shape memory polymers. Compared with thermoplastic polymers, thermosetting shape memory polymers exhibit better strength, higher thermal stability, and faster shape recovery speed due to their covalently cross-linked chemical structure. However, it is precisely because of the existence of their irreversible cross-linked structure that the permanent shape of thermosetting shape memory polymers cannot be reshaped, limiting their diverse applications and development. In order to endow them with the ability to permanently reshape and achieve complex deformations, dynamic covalent bonds are often introduced. For example, Bowman et al. (Science, 2005, 308, 1615-1617) proposed the concept of photoplasticity, which uses light to induce polymer network rearrangement to deform the permanent shape of materials. This method offers remote controllability and high spatial selectivity, but due to poor light penetration, it is not suitable for bulk materials. Xie et al. (Science Advances, 2016, 2, e1501297) synthesized a polycaprolactone network crosslinked with tetrathiol, achieving plastic deformation through thermally induced transesterification. However, dynamic bond exchange reactions at high temperatures also trigger shape recovery, hindering permanent shape reconstruction. Therefore, there is an urgent need to employ stimuli other than heat and light for stress regulation.

[0003] Furthermore, while shape memory polymers (SMPs) offer strong programmability, most suffer from limited reversibility. Consequently, their deformation range is limited, deformation controllability is weak, and response rates are slow. Stimulus-responsive polymers, on the other hand, possess excellent reversibility. Combining these two technologies can simultaneously achieve programmability and reversibility, which is significant for developing more efficient and complex deformations. However, currently, efficient combination strategies are lacking. Meanwhile, durability is also crucial for deformable materials. Shape memory polymers containing dynamic covalent bonds can endow materials with excellent self-healing and recyclability properties. However, because dynamic covalent bonds are easily affected by external stimuli, they often sacrifice the material's mechanical properties. Therefore, designing deformable materials that simultaneously possess high strength, self-healing, and recyclability will further expand their practical application value, but this remains a significant challenge. Summary of the Invention

[0004] To address the aforementioned technical problems, the present invention aims to provide a humidity-responsive deformable dynamic covalent polymer and its preparation method, thereby solving the problems of existing dynamic covalent polymer-based deformable materials having difficulty in achieving complex programmable and reversible deformation behavior and poor durability.

[0005] The technical solution of this invention to solve the above-mentioned technical problems is as follows: A method for preparing a humidity-responsive deformation dynamic covalent polymer is provided, comprising the following steps:

[0006] (1) Dissolve N-vinylamide polymers in an organic solvent to obtain a linear polymer solution;

[0007] (2) In the linear polymer solution obtained in step (1), phenylboronic acid monomer with double bonds, hydrophilic crosslinking agent and initiator are added in sequence, stirred until completely dissolved, and free radical polymerization reaction is carried out to obtain a polymer solution with a semi-interpenetrating network.

[0008] (3) The polymer solution of the semi-interpenetrating network obtained in step (2) is poured into a mold and heated to evaporate the solvent to obtain a humidity-responsive deformation dynamic covalent polymer.

[0009] Based on the above technical solution, the present invention can be further improved as follows:

[0010] Furthermore, in step (1), the mass-to-volume ratio of the N-vinylamide polymer to the organic solvent is 0.2-0.6 g: 8-12 mL.

[0011] Furthermore, in step (1), the N-vinylamide polymer is poly(N-vinyllactam), poly(N-vinylacetamide), or polyvinylpyrrolidone.

[0012] Furthermore, in step (1), the N-vinylamide polymer is polyvinylpyrrolidone.

[0013] Furthermore, in step (1), the organic solvent is N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylethylenediamine, dimethyl sulfoxide, acetone or ethanol.

[0014] Furthermore, in step (2), the mass ratio of the double-bonded phenylboronic acid monomer, the hydrophilic crosslinking agent, and the initiator is 100:10-30:1-2, and the mass ratio of the double-bonded phenylboronic acid monomer and the organic solvent in step (1) is 1-3:100.

[0015] Furthermore, in step (2), the phenylboronic acid monomer with double bonds is acrylamide phenylboronic acid or vinyl phenylboronic acid.

[0016] Furthermore, in step (2), the crosslinking agent is polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, polypropylene glycol diacrylate, or polypropylene glycol dimethacrylate.

[0017] Furthermore, in step (2), the initiator is azobisisobutyronitrile, azobisisovalerate, azobisisoheptanenitrile, or dimethyl azobisisobutyrate.

[0018] Furthermore, in step (2), free radical polymerization is carried out at 65-75℃ for 11-13 hours.

[0019] Furthermore, in step (3), the solvent is heated and evaporated at 50-70°C.

[0020] Furthermore, in step (3), a polytetrafluoroethylene mold is used.

[0021] The present invention also provides a humidity-responsive deformation dynamic covalent polymer prepared by the above method.

[0022] The present invention has the following beneficial effects:

[0023] 1. This invention first involves free radical polymerization of a phenylboronic acid monomer containing double bonds, a crosslinking agent, and an initiator in a solution containing a linear N-vinylamide polymer to obtain a polymer solution with a semi-interpenetrating crosslinked network structure. The solvent is then evaporated to obtain a dynamic covalent polymer. Due to the unique semi-interpenetrating network structure and dynamic boron-oxygen bonds responsive to water / humidity / heat stimulation in this polymer network, the dynamic covalent polymer exhibits excellent mechanical strength, self-healing, recyclability, humidity-induced plastic deformation, thermally responsive shape memory behavior, and humidity-responsive actuation. Furthermore, this dynamic covalent polymer can simultaneously achieve efficient, complex, programmable, and reversible deformation, showing promising application prospects in actuators and flexible robots.

[0024] 2. The boron-oxygen bond of this invention is a dynamic covalent bond that responds to water or humidity. Under the stimulation of humidity or water, the boron-oxygen bond dissociates to generate organic boric acid, which then recombines under dehumidification or drying conditions to form a boron-oxygen bond. This dynamic property allows the covalent polymer of this invention to undergo network recombination under the stimulation of humidity and the action of external forces, resulting in permanent deformation, i.e., humidity-induced solid plastic deformation. This method is simple and controllable, overcoming the shortcomings of existing photoplastic and thermoplastic technologies. At the same time, under the stimulation of humidity, due to the presence of hydrogen bonds and reversible boron-oxygen bonds between the hygroscopic polymer (N-vinylamide polymers and hydrophilic crosslinking agents) and water molecules, this dynamic covalent polymer undergoes reversible deformation through asymmetric expansion, i.e., humidity-responsive deformation. The deformable material of this invention can simultaneously achieve programmability and reversibility, with increased deformation amplitude, enhanced deformation controllability, and faster response rate, providing a new strategy for preparing efficient and complex deformable materials.

[0025] 3. The dynamic boron-oxygen bonds formed by the self-polymerization of phenylboronic acid after dehydration endow the polymer with excellent self-healing and recyclability properties. Combined with the permanent cross-linking network formed by the cross-linking agent, it realizes the thermally responsive shape memory properties based on humidity-induced plasticity. In addition, by utilizing the hygroscopicity of N-vinylamide polymers and the water-induced dynamic changes of boron-oxygen bonds, the prepared dynamic polymer film has sensitive humidity-responsive deformation behavior, providing an effective new strategy for the precise control of stimulus-responsive actuation behavior and the programmable deformation behavior of shape memory polymers.

[0026] 4. The dynamic covalent polymer prepared by this invention combines the advantages of high strength, self-healing, shape memory, and recyclability. Specifically, it boasts a tensile strength of up to 52.3 MPa, a self-healing efficiency of up to 99%, a shape recovery rate of up to 97%, and can be recycled at least three times. This invention introduces dynamic boron-oxygen bonds into the shape memory polymer, utilizing the humidity-sensitive nature of these bonds to achieve humidity-induced plastic deformation. That is, under humidity stimulation, the initial shape of the shape memory polymer can be reshaped. This method is easy to operate, safe, and simple. Because the dynamic polymer film has strong hygroscopicity, it can undergo asymmetrical expansion and bending deformation through humidity stimulation, showing potential application value in the field of humidity-responsive actuators. Attached Figure Description

[0027] Figure 1 The tensile stress-strain diagram of the dynamic covalent polymer in Example 1;

[0028] Figure 2 An optical microscope image of the dynamic covalent polymer self-healing process in Example 1;

[0029] Figure 3 This is a comparison diagram of tensile stress-strain after the dynamic covalent polymer in Example 1 has been recycled;

[0030] Figure 4 This is a graph showing the shape fixation rate and shape recovery rate of the dynamic covalent polymer in Example 1;

[0031] Figure 5 This is a diagram showing the humidity-induced solid plastic deformation and thermal response shape memory behavior of the dynamic covalent polymer in Example 1;

[0032] Figure 6 This is a humidity-responsive deformation diagram of the dynamic covalent polymer in Example 1. Detailed Implementation

[0033] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer should be followed. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0034] Example 1:

[0035] A humidity-responsive deformation dynamic covalent polymer, the preparation method of which includes the following steps:

[0036] (1) Dissolve 0.4 g of poly(N-vinyl lactam) in 10 mL of organic solvent N,N-dimethylacetamide to obtain a linear polymer solution;

[0037] (2) In the linear polymer solution obtained in step (1), 0.1g of vinylphenylboronic acid, 20mg of crosslinking agent polypropylene glycol diacrylate and 2mg of initiator azobisisovalerate are added in sequence to completely dissolve and obtain a uniform mixed solution. Then, the solution is placed in a nitrogen atmosphere and free radical polymerized at 70°C for 12h to obtain a polymer solution with a semi-interpenetrating network.

[0038] (3) The polymer solution of the semi-interpenetrating network obtained in step (2) is poured into a polytetrafluoroethylene mold and heated at 60°C to evaporate the solvent, thus obtaining the dynamic covalent polymer.

[0039] Example 2:

[0040] A humidity-responsive deformation dynamic covalent polymer, the preparation method of which includes the following steps:

[0041] (1) Dissolve 0.6 g of poly(N-vinylacetamide) in 10 mL of organic solvent N,N-dimethylacetamide to obtain a linear polymer solution;

[0042] (2) In the linear polymer solution obtained in step (1), 0.2g of vinylphenylboronic acid, 60mg of crosslinking agent polypropylene glycol diacrylate and 3mg of initiator azobisisovalerate are added in sequence to completely dissolve and obtain a uniform mixed solution. Then, the solution is placed in a nitrogen atmosphere and subjected to free radical polymerization at 65°C for 11h to obtain a polymer solution with a semi-interpenetrating network.

[0043] (3) The polymer solution of the semi-interpenetrating network obtained in step (2) is poured into a polytetrafluoroethylene mold and heated at 50°C to evaporate the solvent, thus obtaining the dynamic covalent polymer.

[0044] Example 3:

[0045] A humidity-responsive deformation dynamic covalent polymer, the preparation method of which includes the following steps:

[0046] (1) Dissolve 0.8g of polyvinylpyrrolidone in 10mL of organic solvent N,N-dimethylacetamide to obtain a linear polymer solution;

[0047] (2) In the linear polymer solution obtained in step (1), 0.3g of vinylphenylboronic acid, 50mg of crosslinking agent polypropylene glycol diacrylate and 6mg of initiator azobisisovalerate are added in sequence to completely dissolve and obtain a uniform mixed solution. Then, the solution is placed in a nitrogen atmosphere and free radical polymerized at 75°C for 13h to obtain a polymer solution with a semi-interpenetrating network.

[0048] (3) The polymer solution of the semi-interpenetrating network obtained in step (2) is poured into a polytetrafluoroethylene mold and heated at 70°C to evaporate the solvent, thus obtaining the dynamic covalent polymer.

[0049] Test case

[0050] I. Mechanical property testing

[0051] The dynamically covalently bonded polymer obtained in Example 1 was cut into rectangular strips of uniform size (50mm × 2mm × 1mm). The strips were then stretched using a universal stretching machine (Instron 5965, Norwood, MA) at a depth of 50mm. -1 The tensile test was conducted at the specified speed under environmental conditions (approximately 25°C, 25% RH). Each group of specimens underwent at least three repeated parallel tensile tests. The results are shown in […]. Figure 1 .

[0052] Depend on Figure 1 It is known that the dynamic covalent polymer obtained by this invention has a tensile strength as high as 38.5 MPa, exhibiting excellent mechanical properties.

[0053] II. Self-healing performance test

[0054] A scalpel was used to make a scratch on the surface of the dynamic covalent polymer prepared in Example 1, and half a drop of water was placed on the scratch. The surface was then left under ambient conditions (approximately 25°C, 25% RH) for 6 hours. The self-healing process of the crack at different time points was recorded using an optical microscope. The results are shown in [Figure number missing]. Figure 2 .

[0055] Depend on Figure 2 It can be seen that the crack gradually decreases with time, and the crack basically disappears after 6 hours of healing, indicating that the dynamic covalent polymer prepared by this invention has good self-healing properties.

[0056] III. Recyclability Performance Test

[0057] The dynamic covalent polymer obtained in Example 1 was cut into small fragments with scissors. 1.8 g of the fragments was weighed and dissolved in a mixed solvent of 10 mL DMF and 1 mL deionized water. The solution was ultrasonically stirred at room temperature until completely dissolved. The polymer solution was then poured into a polytetrafluoroethylene mold and dried in a 70°C oven for 4 days until the solvent completely evaporated. The recovered polymer was obtained by peeling it off the mold. The recovered sample was tested using a testing machine at 50 mm / min. -1 The speed was measured, and tensile tests were conducted under environmental conditions (25℃, 25%RH), repeated 3 times. The results are shown in [Figure number missing]. Figure 3 .

[0058] Depend on Figure 3 It can be seen that the tensile stress-strain curves of the sample and the original sample after multiple recycling show that the tensile strength can still reach 35.3 MPa after three recyclings, indicating that the dynamic covalent polymer prepared by this invention has good recyclability.

[0059] IV. Shape Memory Performance Test

[0060] The dynamic covalent polymer obtained in Example 1 was quantitatively characterized for shape memory efficiency using a bending method. Specifically, the dynamic covalent polymer was cut into rectangular strips of uniform size (35mm × 2mm × 0.3mm), softened at different temperatures (60℃, 70℃, 80℃, and 90℃), and bent into a "U" shape under external force. The initial bending angle of the sample was θ0 (180°). The sample was then cooled to 25℃ to maintain a temporary shape (the angle of deformation was recorded as θ). f Shape fixation rate (R) f ) is θ f Percentage relative to θ0;

[0061] When the deformed spline is reheated at different temperatures (60℃, 70℃, 80℃, and 90℃), the temporary "U" shape will return to its initial shape. Simultaneously, the angle (θ) of the spline changing over time is recorded. r Shape recovery rate (R) r ) is θ f and θ r The difference between θ f The percentage, the results are shown in [link to results]. Figure 4 .

[0062] Depend on Figure 4 It can be seen that the shape fixation rate and shape recovery rate of the dynamic covalent polymer prepared by this invention increase with increasing temperature, and the highest R can be achieved at 90℃. r and R f .

[0063] V. Shape Memory Performance Testing Based on Humidity-Induced Plasticity

[0064] The dynamic covalent polymer obtained in Example 1 was prepared into a planar square film (5 cm long, 5 cm wide, and 0.3 mm thick). It was placed under high humidity (RT, 90% RH) conditions for 24 hours, and then folded into a "flower" shape using origami techniques. After removing the external force, the shape could not be restored to its initial planar state. After drying under low humidity (RT, 20% RH) conditions for 24 hours, a 3D structure with a permanent "flower" shape was obtained. The "flower" shaped film was softened at 90°C, and then unfolded into a temporary 2D planar film shape under external force. It was then cooled to 25°C to maintain the temporary shape. Only when the sample with this temporary shape was placed back at 90°C would it restore its initial "flower" shape. The results are shown in […]. Figure 5 .

[0065] Depend on Figure 5 It is known that traditional shape memory behavior can only program its temporary shape, while humidity-induced solid plastic deformation can reshape the initial shape of shape memory polymers using mild, low-energy humidity. Therefore, it increases the complexity of the shape of shape memory polymers themselves, solves the problem that traditional polymer molding and processing is easily limited by molds and demolding, making it difficult to produce complex and delicate permanent shapes, and expands the application range of shape memory polymers.

[0066] VI. Humidity Response Deformation Test

[0067] The dynamic covalent polymer film prepared in Example 1 was placed on a fabric substrate containing water vapor. Due to the asymmetrical expansion of the polymer film, the originally flat polymer film curled up in the direction away from the water vapor. After the water vapor on the fabric substrate was removed, the film returned to its initial planar state from the curled state. The results are shown in [the figure]. Figure 6 .

[0068] Depend on Figure 6 It is known that the dynamic covalent polymer prepared by the present invention can be shaped like a rope catcher, bend under humidity stimulation, and return to a flat state after dehumidification, thus simulating the closing and opening of the rope catcher.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a humidity-responsive deformation dynamic covalent polymer, characterized in that, Includes the following steps: (1) Dissolve N-vinylamide polymers in an organic solvent to obtain a linear polymer solution; (2) In the linear polymer solution obtained in step (1), phenylboronic acid monomer with double bonds, hydrophilic crosslinking agent and initiator are added in sequence, stirred until completely dissolved, and free radical polymerization reaction is carried out to obtain a polymer solution with a semi-interpenetrating network. (3) The polymer solution of the semi-interpenetrating network obtained in step (2) is poured into a mold and heated to evaporate the solvent to obtain a humidity-responsive deformation dynamic covalent polymer.

2. The method for preparing the humidity-responsive deformation dynamic covalent polymer according to claim 1, characterized in that, In step (1), the mass-volume ratio of N-vinylamide polymer to organic solvent is 0.2-0.6 g: 8-12 mL.

3. The method for preparing the humidity-responsive deformation dynamic covalent polymer according to claim 1, characterized in that, In step (1), the organic solvent is N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylethylenediamine, dimethyl sulfoxide, acetone or ethanol.

4. The method for preparing the humidity-responsive deformation dynamic covalent polymer according to claim 1, characterized in that, In step (2), the mass ratio of the double-bonded phenylboronic acid monomer, the hydrophilic crosslinking agent and the initiator is 100:10-30:1-2, and the mass ratio of the double-bonded phenylboronic acid monomer and the organic solvent in step (1) is 1-3:

100.

5. The method for preparing the humidity-responsive deformation dynamic covalent polymer according to claim 1, characterized in that, In step (2), the phenylboronic acid monomer with double bonds is acrylamide phenylboronic acid or vinyl phenylboronic acid.

6. The method for preparing the humidity-responsive deformation dynamic covalent polymer according to claim 1, characterized in that, In step (2), the crosslinking agent is polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, polypropylene glycol diacrylate or polypropylene glycol dimethacrylate.

7. The method for preparing the humidity-responsive deformation dynamic covalent polymer according to claim 1, characterized in that, In step (2), the initiator is azobisisobutyronitrile, azobisisovalerate, azobisisoheptanenitrile, or dimethyl azobisisobutyrate.

8. The method for preparing the humidity-responsive deformation dynamic covalent polymer according to claim 1, characterized in that, In step (2), free radical polymerization is carried out at 65-75℃ for 11-13 hours.

9. The method for preparing the humidity-responsive deformation dynamic covalent polymer according to claim 1, characterized in that, In step (3), the solvent is heated and evaporated at 50-70°C.

10. The humidity-responsive deformation dynamic covalent polymer prepared by the method of any one of claims 1-9.